Soil biogeochemistry in the Anthropocene: necessity and possibility - Dmytruk, Y.M. (AgroChemistry and Soil Science, 2018)
The intensity of transformation of the Biosphere components in recent decades suggests a fundamental change in natural process and trends by anthropogenic, which allowed scientists to select Anthroposphere. The Anthroposphere formed in the time stage, called the Anthropocene. Human health and environmental health must be assessed keeping in mind the ecosystem services in which soils have an exceptional role; also importance of soil cover in the Biosphere is unique. Biogeochemistry interactions in soils are occurring on different levels and different time scale. Soil cover under anthropogenic impact has bigger heterogeneity, so it complicates evaluation of Biogeochemistry status. Hence, the microbiota has an exceptional significance. Therefore, understanding the functions of soil cover in the Biosphere and towards achieving a sustainability of ecosystem services without considering of microbiota activity is impossible. This requires a restructuring of the research methodology, taking into account the modern equipment and approaches. In particular, the analysis of environmental risks needs the transformation of survey schemes, and soil indicators should be the defining factor in the sampling strategy. In addition, there is an increasing role of cartographic modeling and zoning based on innovative software products, which combines computation, analysis, interpolation and the actual simulation of the content and behavior of chemical elements in soils for specific application requests and for management in general. Establishing maximum allowable concentrations based on ecotoxicological studies is a great challenge. Therefore, the use of background values or threshold levels remains controversial. It is clear that the nature of the biogeochemical parameters of the soil cover is concrete-regional rather than general for any territories.